Focal choroidal excavation: review of literature. Issue 8 (11th August 2020) - Verma, Saurabh; Kumar, Vinod; Azad, Shorya; Bhayana, Amber Amar; Surve, Abhidnya; Kumar, Suneel; Agarwal, Pulak; Chawla, Rohan; Venkatesh, Pradeep
Abstract : Focal choroidal excavation (FCE) is defined as an area of concavity in choroid detected on optical coherence tomography. These are mostly present in macular region without evidence of accompanying scleral ectasia or posterior staphyloma. Though initially considered to be congenital, increasing number of cases have been identified in association with other choroidal pathologies such as central serous choroidopathy, choroidal neovascularisation, polypoidal choroidal vasculopathy, choroiditis, choroidal tumours. In this review article, we aim to elaborate on the morphology, pathogenesis and differential diagnosis of FCE and specifically discuss the spectrum of diseases with known association along with the impact of their treatment on FCE